The Handling of the Corona Virus Pandemic (COVID-19) in Terms of Religious Aspects for Women Reciting Ar-Ridho in the Village of Tanjung Morawa, Tanjung Morawa District - Nasution, Khairina; Pujiati; Khairawati; Rahimah (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This public servive is conducted by the team of Faculty of Cultural Studies, The University of Sumatera Utara with Ar-Ridho women gatherings, Tanjung Morawa. They have not yet fluently read the Koran Verses (Juz 30) and safe short prayers, and still reluctant to come to the gatherings due to being afraid of the pandemic era. It is aimed to describe methods to overcome corona virus through religious aspects to Ar-Ridho women gatherings. It is expected they are able to approach Allah so that they have high surrender. Being calm can increase body immunity that make them possess self-confidence to attend the gatherings once a week. The methods adopted are lectures, discussion, and demonstration. To solve the problems the team give the Koran reading materials and safe prayers with their meanings. The women, then, are asked to repeat the reading. The results show they have been able to read the Koran and short prayers, and understand the meanings so that they can feel peaceful, calm, and finally it can make their body immunity stronger. The team, then, give lessons like the above way once in a month so that it can lead to be quiet and pleasant in the society.